Simulation of Groundwater-Level Behavior in Southeast Region of Korea Induced by 2016 Gyeong-Ju Earthquake Using 2D Hydro-Mechanical Coupled Bonded Particle Modeling - Hyunjin Cho; Se-Yeong Hamm; Jeoung Seok Yoon; Soo-Gin Kim; Jae-Yeol Cheong (Applied Sciences)
This study examines the hydrogeological response to the 12 September 2016 Gyeong-Ju earthquake (ML 5.8) in the southeastern region of the Korean Peninsula. Using 2D hydro-mechanical coupled bonded particle modeling, we simulated the dynamic fault rupture process to analyze stress redistribution and its impact on pore pressure and groundwater levels (GWLs). The results indicated that compressional areas correlated strongly with pore pressure increases and GWL rises, while extensional areas showed decreases in both. Observations from the groundwater monitoring Well 5 at Gyeong-Ju San-Nae and Well 8 at Gyeong-Ju Cheon-Buk, located approximately 15 km from the earthquake’s epicenter, aligned well with the model’s predictions and interpretation, providing validation for the simulation. These findings highlight the capability of hydro-mechanical models to capture fault-induced hydrological responses and offer valuable insights into the interplay between seismic activity and groundwater systems.